Pembangunan Aplikasi Pelaporan Perijinan dengan Online Analytical Processing (OLAP) - Dimara Kusuma Hakim (JUITA : Jurnal Informatika, 2011)
Business licensing data in a district that has been collected in a database, it will be useful when it is analyzed, so a lot of important information will be obtained. The government need a system that can help them to analyze data easily. Online Analytical Processing (OLAP) is an implementation of Data warehousing that can help reporting and analyzing well. OLAP can map the data with cube dimensions, each dimension can be easily compared, so the decision maker can find the problems that faced easily and quickly. Some of the problems that solved in this research are : Progress Report on Company Registration in several years, the Number of Companies by the type of business, Development of Investment, the number of SIUP by District, , the number of SIUP by business class, the number of license based on its type, Construction Permit (IMB) in several years, and the Number of Disorders Permits (HO) by several classification. Reporting application in data Licensing are built in this research with OLAP technology.  Based on the Chi-Square testing performed for business licensing data which contain 100-1161 records, the Chi-Square value are 45,89 – 80, greater than Chi-Square table (13,28), there is significantly different for time consuming between SQL and OLAP.  When data are reduced for 90 records, the Chi-Square value is 2.01, less than Chi-Square table, there is no significantly different for time consuming between SQL and OLAP